1976
DOI: 10.1093/oxfordjournals.aje.a112223
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Infections I. Surveillance in a University Hospital

Abstract: A new system of surveillance is described for detecting hospital-aquired infections. Surveillance begins on the ward where a weekly review of the nursing care plan (Kardex) is used to select high risk patients (approximately 65% of the total population) for a subsequent chart review. A nurse-epidemiologist required 16-25 hr per week to perform surveillance and 4 more hr to organize line listings of infected patients. The Kardex review was 82 to 94 percent accurate in detecting nosocomial infections when compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
9

Year Published

1978
1978
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(47 citation statements)
references
References 0 publications
2
36
0
9
Order By: Relevance
“…Estes foram selecionados de acordo com quatro critérios, semelhantes aos utilizados por Wenzel (1976): diagnósticos (leucemia, linfoma, granulocitopenia, diabetes, AIDS, dermatose extensa); resultados de laboratório (hemocultura positiva); procedimentos invasivos (sonda vesical, catéter venoso central, cânula endotraqueal, traqueostomia, cirurgia de grande e médio porte); e tempo de internação (maior ou igual a sete dias). Além dos pacientes portadores de quaisquer destas características, foram também acompanhados todos os internados nas Unidades de Terapia Intensiva e Berçário de Alto Risco.…”
Section: Metodologiaunclassified
See 2 more Smart Citations
“…Estes foram selecionados de acordo com quatro critérios, semelhantes aos utilizados por Wenzel (1976): diagnósticos (leucemia, linfoma, granulocitopenia, diabetes, AIDS, dermatose extensa); resultados de laboratório (hemocultura positiva); procedimentos invasivos (sonda vesical, catéter venoso central, cânula endotraqueal, traqueostomia, cirurgia de grande e médio porte); e tempo de internação (maior ou igual a sete dias). Além dos pacientes portadores de quaisquer destas características, foram também acompanhados todos os internados nas Unidades de Terapia Intensiva e Berçário de Alto Risco.…”
Section: Metodologiaunclassified
“…O maior número de pacientes e episódios de infecção hospitalar identificados pela busca ativa, neste estudo, confirma os resultados de outros autores (Haley, 1986;Hofherc, 1979;Wenzel, 1976). As diferenças encontradas entre a busca ativa e a notificação podem ser explicadas pelas características específicas de cada método.…”
Section: Discussão E Conclusõesunclassified
See 1 more Smart Citation
“…3 Son diversos los investigadores, además de los Centros para la Prevención y el Control de Enfermedades (CDC) de Estados Unidos de América (EUA), que proponen vigilar a todos los pacientes en todo el hospital. [4][5] No obstante, ya que no es posible, en términos prácticos y reales, revisar a todos los pacientes que ingresan al hospital, para detectar IN, se recomienda utilizar fuentes indirectas que permitan la detección de casos de infección; éstas incluyen: la revisión de los cultivos de microbiología, las indicaciones de antibióticos, las curvas de temperatura y el examen de pacientes con factores de riesgo para el desarrollo de infecciones, entre otras. 6 Si bien en otras instituciones este sistema ha tenido una sensibilidad de 82% y ha resultado sumamente eficaz, se recomienda su validación inicial y periódica contra un estándar.…”
Section: Introductionunclassified
“…Thus, to ensure the comparability of HAI rates within a surveillance system, the methods for case finding and ascertainment should be defined [208]. For instance, the sensitivity of a systematic chart review of all patients -a very time-consuming method -has been reported to be as high as 94% [209][210][211], but to drop to 71% if the chart review is selected based on the ward liaison and a review of laboratory reports [212]. The sensitivity of a single method may also vary depending on infection type or patient subpopulation.…”
Section: Case Finding and Ascertainmentmentioning
confidence: 99%